A Comparative Clinical Study on the Efficacy of Oral Sarasvata Ghrita and Sarasvata Ghrita Nasya in the Management of Vataja Shirah Shoola W. S. R. of Tension Headache - Senadheera, T; Samarakoon, S M S; Jayasuriya, HSV (International Research Journal of Ayurveda & Yoga, 2025)
Introduction: Acharya Charaka considered Shiro-ruk as a separate disease in 80 types of Nanatmaja Vata- Vyadhi. He has mentioned five types of Shiroroga (Headache) including Vataja Shiroroga. Considering the line of treatment, Charaka recommended specific ghee preparations for Vatika Shiroroga. Vataja Shirah Shoola (VSS) can be correlated with tension headache which is the most common type of headache. The prevalence of tension headache is about 3% of the general population. Methodology: The present study is a comparative clinical study on the efficacy of oral Sarasvata Grita (SG) and Sarasvata Ghrita Nasya (SGN) on Vataja Shirah Shoola. Thirty patients were selected from the OPD of Ayurveda Hospital, Meegoda and were randomly divided into two groups: group A and group B. Group A was treated with oral SG, 10 ml orally twice a day before meals for a period of 30 days while group B was treated with SGN at the dose of 8 drops daily at 9.00 am after a light meal for same duration. Patients were evaluated before and after treatment. Data were analyzed using SPSS statistical software. Results: The result revealed that the 36 – 45 age group (76.7%), female (56.7%), and Vata-pitta prakriti (56%) are more vulnerable to VSS. Oral SG improved subjective parameters and blood pressure in a highly significant manner (P > 0.001) whereas oral SG improved bi-temporal headache and disturbed sleep in a significant manner (P < 0.05). Disscussion and Conclusion: Collectively, the ingredients of SG have tridosha shamaka effect, especially Vata shamaka effect. Due to synergistic effect of SG, most of the parameters have shown significant improvement. SGN improved subjective parameter in significant manner (P < 0.05) whereas the improvement of blood pressure is highly significant (P < 0.001). When comparing the effect of two treatments on VSS, it is reported that the difference of mean of most of the subjective parameters between group A and B is highly significant (P < 0.001). Hence, it is concluded that oral Sarasvata Ghrita has higher degree of efficacy on Vataja Shirahshoola over Sarasvata Ghrita Nasya.